Evaluation of Dyclonine Hydrochloride Mucilage for Pain Control in Plaque Control‐Oriented Periodontal Therapy: A Double‐Blind Randomised Clinical Trial - Zeng Yi; Zhou Hangfan; Huang Rongli; Wu Zixiang; Chu Xiangyuan; Yang Jiantang; Yang Kun; Yan Fuhua; Ge Song (International Journal of Dental Hygiene, 2026)
ABSTRACT Objective To evaluate the effectiveness of dyclonine hydrochloride mucilage (DYC) in controlling pain during guided biofilm therapy (GBT) and its potential to improve patient comfort and adherence to regular supportive periodontal treatment. Methods Patients aged 18–65 years undergoing GBT were enrolled in this randomised, double‐blind, split‐mouth placebo‐controlled study. The left and right sides of the mouth were randomly assigned to the control or experimental group using a coin toss. The Modified Dental Anxiety Scale was completed before the procedure. In the control group, cotton balls soaked in a 1:1 mixture of normal saline and 3% hydrogen peroxide were applied to the mucosa and gingiva for 1 min before supragingival scaling, air polishing, and periodontal probing. In the experimental group, patients rinsed with DYC for 3 min before undergoing the same procedures. After treatment, patients completed a numeric rating scale to assess pain. Neither the patients nor the operator was aware of the treatment allocation. Non‐parametric tests and generalised linear models were used to analyse changes in pain scores and factors associated with the anaesthetic effect. Results Pain scores during GBT were significantly reduced with DYC. The median (interquartile range) changes in pain scores were: supragingival scaling, 1.0 (0.0–1.0); air polishing, 1.0 (0.0–1.0); and periodontal probing, 0.0 (0.0–1.0). Patients with dental anxiety experienced more reductions in pain scores than those without. The ratio of patients willing to use anaesthetics to those unwilling was 2:1. Conclusion DYC effectively reduces pain during GBT, with a more pronounced effect in patients with dental anxiety. DYC may represent a promising option for pain control during GBT.